Assessing the knowledge and opinions of registered nurses with reference to quality indicators in clinincal nursing within a tertiary health institution in Saudi Arabia - Pelser, Anya (Stellenbosch : Stellenbosch University, 2011)
Thesis (MCur)--Stellenbosch University, 2011.